External reference pricing for medicines in Ukraine: latest trends - Kucherenko, L. I.; Nizhenkovska, I. V.; Sholoiko, N. V.; Hala, L. O.; Datsiuk, N. O.; Кучеренко, Людмила Іванівна; Ніженковська, І. В.; Шолойко, Н. В.; Гала, Л. О.; Дацюк, Н. О. (Запорізький державний медико-фармацевтичний університет, 2023)
The aim of this study is to analyze the current status of ERP implementation in Ukraine and provide recommendations for improving this policy. Materials and methods. During the research process, an analysis of the ERP’s current regulatory framework was conducted, and ERP implementation in Ukraine was assessed according to adherence to the 14 best practice principles of ERP proposed by Sullivan, Kanavos & Kalo in 2015. Results. In Ukraine, ERP has been introduced for medicines from the National Essential Medicine Lists (NEML) and the “Affordable Medicines” program. The Ministry of Health (MoH) of Ukraine has approved a Register of marginal wholesale prices for medicines purchased with state budget funds and subject to price regulation. Currently, the register includes 1239 medicinal products, of which 1233 are from NEML and 6 have undergone Health Technology Assessment (HTA). Approximately 58 % of medicines have a set price through ERP, 24 % are regulated by internal reference pricing (IRP), and nearly 18 % have declared prices. This indicates a lack of uniformity in approaches to price regulation for medicines and requires further improvements. According to the latest update of the Register of medicines for reimbursement under the state medical guarantees program, there are 486 medicines, including 72 insulins and 21 immunosuppressive medicines (184 medicines are provided with co-payment). Different approaches, including different reference countries and price calculation algorithms, are applied for the price regulation of medicines in NEML and the “Affordable Medicines” program. An assessment of the implementation of the ERP system in Ukraine based on the 14 best practice principles of ERP proposed by Sullivan, Kanavos & Kalo in 2015 showed that the current policy does not adhere to all principles. Мета роботи – аналіз сучасного стану впровадження зовнішнього РЦ на ЛЗ в Україні та надання рекомендацій для покращення цієї практики. Матеріали та методи. У процесі дослідження проаналізували чинну нормативно-правову базу щодо зовнішнього РЦ, оцінили впровадження зовнішнього РЦ в Україні згідно з 14 принципами зовнішнього РЦ, що запропоновані Sullivan, Kanavos & Kalo в 2015 році. Результати. В Україні запроваджено зовнішнє РЦ для ЛЗ із Національного переліку основних лікарських засобів (Нацперелік) та програми «Доступні ліки». МОЗ України затверджено Реєстр граничних оптово-відпускних цін на деякі ЛЗ, які закуповуються за кошти державного бюджету та підлягають регулюванню цін. Нині реєстр включає 1239 лікарських засобів: 1233 ЛЗ – із Нацпереліку, 6 ЛЗ, – які пройшли оцінювання медичних технологій. Майже 58 % ЛЗ мають встановлену ціну через зовнішнє РЦ, 24 % ЛЗ регулюються внутрішнім РЦ, майже 18 % ЛЗ задекларували ціни. Це свідчить про неоднорідність підходів до регулювання цін на ЛЗ і потребує вдосконалення. Згідно з останнім оновленням Реєстру лікарських засобів, які підлягають відшкодуванню за програмою державних медичних гарантій, індексують 486 найменувань, включаючи 72 найменування інсулінів і 21 найменування імуносупресивних препаратів (184 найменування – із доплатою). Для регулювання цін на ЛЗ у Нацпереліку та програмі «Доступні ліки» застосовують різні підходи, включаючи різну кількість референтних країн і різні алгоритми розрахунку цін. Оцінювання впровадження системи зовнішнього РЦ в Україні на основі методології ефективного впровадження зовнішнього РЦ, яку запропонували Sullivan, Kanavos & Kalo у 2015 році, показало: чинна система не відповідає всім принципам ефективного зовнішнього РЦ.
Зовнішнє референтне ціноутворення на лікарські засоби в Україні: останні тенденції
Kucherenko L. I. - ORCID ID: 0000-0003-2229-0232
Keywords: pharmaceutical preparations; reference prices; external reference pricing; health technology assessment; лікарські засоби; референтне ціноутворення; зовнішнє референтне ціноутворення; оцінка медичних технологій